2016
DOI: 10.1007/s10339-015-0747-0
|View full text |Cite
|
Sign up to set email alerts
|

Imageability and semantic association in the representation and processing of event verbs

Abstract: This study examined the relative salience of imageability (the degree to which a word evokes mental imagery) versus semantic association (the density of semantic network in which a word is embedded) in the representation and processing of four types of event verbs: sensory, cognitive, speech, and motor verbs. ERP responses were recorded, while 34 university students performed on a lexical decision task. Analysis focused primarily on amplitude differences across verb conditions within the N400 time window where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The action effect observed in the present study is consistent with several studies that have shown the involvement of the motor cortex during the reading of action verbs using fMRI [10,33], EEG [25,32,34], behavioral measures [13][14][15][16]25] and TMS [29,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The action effect observed in the present study is consistent with several studies that have shown the involvement of the motor cortex during the reading of action verbs using fMRI [10,33], EEG [25,32,34], behavioral measures [13][14][15][16]25] and TMS [29,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…The same applies to action language, such that semantic information referring to an action would engage the sensory motor system. To better understand this link, researchers have probed the involvement of the motor system during action language processing using various methodologies, such as functional Magnetic Resonance Imaging (fMRI) (Hauk et al 2004; Pulvermüller et al 2005; Aziz-Zadeh et al 2006; Van Dam, Rueschemeyer, and Bekkering 2010; although for critical views see: de Zubicaray et al 2013; Wurm and Caramazza 2019), electroencephalogram (EEG) (Kellenbach et al, 2002; Pulvermüller et al, 2001; Xu et al, 2016), behavioral measures (Andres et al, 2015; Klepp et al, 2019; Pulvermüller et al, 2001; Rabahi et al, 2012, 2013) and Transcranial Magnetic Stimulation (TMS) (Papeo et al 2009, 2015; Labruna et al 2011; Scorolli et al 2012; Innocenti et al 2014; see review: Papeo et al 2013). Specifically, Hauk et al (2004) using fMRI reported that silent reading of action words leads to somatotopic activation of the effector-related representation within the primary motor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…These collections of ratings provide important psycholinguistic information about Chinese words, but are limited in scale relative to resources available in other languages. This leaves researchers to collect their own AoA ratings for whatever is needed in their individual research projects (e.g., Bai, Ma, Dunlap, & Chen, 2013;Chen, Dent, You, & Wu, 2009;Crepaldi, Che, Su, & Luzzatti, 2012;Law & Yeung, 2010;Xu, Kang, & Guo, 2016;Yu, Law, Han, Zhu, & Bi, 2011) and certainly weakens comparability across studies. To fill the void, the present study reports AoA ratings for 19,716 simplified Chinese words.…”
Section: Aoa Ratingsmentioning
confidence: 99%
“…Both Yao et al [31] and Yee [32] had collected imageability ratings. Xu, Kang, and Guo [40] also collected imageability ratings for a set of two-character Chinese words stimuli. Correlation coefficients between concreteness and imageability ratings are presented in Table 2.…”
Section: Correlation Between the Present And Past Concreteness Ratingsmentioning
confidence: 99%